Adsorption of H₂, O₂, H₂O, OH and H on monolayer MoS₂ - Ferreira, Fábio (2018)
Hydrogen and hydrogen-containing gases are commonly used as reductants in chemical vapor deposition (CVD) growth of MoS2. Here, we consider the defects resulting from the presence of hydrogen during growth and the resulting electronically active defects. In particular, we find that the interstitial hydrogen defect is a negative-$U$ center with amphoteric donor and acceptor properties. Additionally, we consider the effects of the interaction with water and oxygen. The defects are analysed using density functional theory calculations.